2018
DOI: 10.2320/matertrans.m2018051
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Aluminum–Tungsten Alloy Films Using EMIC–AlCl<sub>3</sub>–W<sub>6</sub>Cl<sub>12</sub> Ionic Liquids of Different Compositions

Abstract: Electrodeposition of AlW alloy films with high W contents has been carried out using 1-ethyl-3-methylimidazolium chloride (EMIC) aluminum chloride (AlCl 3) ionic liquids containing tungsten(II) chloride (W 6 Cl 12). Although the corrosion resistance and hardness of the alloy films are expected to be improved with an increase in the W content, dense films with W contents higher than ³12 at% have not been obtained by electrodeposition to date. This study has demonstrated that electrodeposition using a EMICAlCl 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Among aluminum-based binary alloys, Al–W alloys are known to have the highest resistance to chloride-induced pitting corrosion 4,5 . Al–W alloys have been formed using sputtering 411 , ion implantation 12 , laser alloying 13 , and electrodeposition 1419 . Electrodeposition is advantageous for industrial applications because a thick film can be formed rapidly on a large substrate using uncomplicated equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among aluminum-based binary alloys, Al–W alloys are known to have the highest resistance to chloride-induced pitting corrosion 4,5 . Al–W alloys have been formed using sputtering 411 , ion implantation 12 , laser alloying 13 , and electrodeposition 1419 . Electrodeposition is advantageous for industrial applications because a thick film can be formed rapidly on a large substrate using uncomplicated equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Electrodeposition is advantageous for industrial applications because a thick film can be formed rapidly on a large substrate using uncomplicated equipment. Recently, we reported that dense Al–W alloy films with W contents of up to 18 at.% could be electrodeposited from 1-ethyl-3-methylimidazolium chloride (EMIC)–aluminum chloride (AlCl 3 ) ionic liquids containing tungsten(II) chloride (W 6 Cl 12 ) 1719 .…”
Section: Introductionmentioning
confidence: 99%